Repainting the little red schoolhouse : a history of Eastern German education, 1945-1995 - Rodden, John (OUP E-Books., 2002)
This is the first English-language study of GDR education and the first book, in any language, to trace the history of Eastern German education from 1945 through the 1990s. Rodden fully relates the GDR's attempt to create a new Marxist nation by means of educational reform, and looks not only at the changing institution of education but at something the Germans call Bildung--the formation of character and the cultivation of body and spirit. The sociology of nation-building is also addressed.